2014
DOI: 10.4236/jdm.2014.41005
|View full text |Cite
|
Sign up to set email alerts
|

Role of toll receptors in diabetic nephropathy

Abstract: Objectives: Diabetic nephropathy is the leading cause of chronic kidney disease. The pathogenesis of DN remains incompletely understood. It has been recently demonstrated that inflammatory processes play a significant role in the development and progression of DN. Toll-like receptors play a fundamental role in the innate immune system by triggering proinflammatory signaling pathways. Our aim is to evaluate the expression of TLRs on monocytes and relate their expression with inflammation in HD patients with & w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
0
0
1
Order By: Relevance
“… Lin et al (2012) showed increased expression of TLR4 in human proximal tubular epithelial cells under hyperglycaemic conditions, pointing toward a role of TLR4 in tubulointerstitial inflammation in DNP. Also, our results agreed with the study of Mansour et al (2014) , which concluded that the level of TLR2 and 4 is elevated in patients with end-stage DNP compared to that of patients with end-stage renal disease due to non-DNP. Badr et al (2019) found that TLRs were overexpressed in microvascular complicated type 2 diabetic patients as compared to non-complicated type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 92%
“… Lin et al (2012) showed increased expression of TLR4 in human proximal tubular epithelial cells under hyperglycaemic conditions, pointing toward a role of TLR4 in tubulointerstitial inflammation in DNP. Also, our results agreed with the study of Mansour et al (2014) , which concluded that the level of TLR2 and 4 is elevated in patients with end-stage DNP compared to that of patients with end-stage renal disease due to non-DNP. Badr et al (2019) found that TLRs were overexpressed in microvascular complicated type 2 diabetic patients as compared to non-complicated type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 92%
“…Secara tragis, diabetes dapat mengakibatkan 4,9 juta kematian per tahun (IDF 2015). Hal ini disebabkan komplikasi diabetik meliputi neuropati, disfungsi erektil, nefropati, retinopati, makroangiopati seperti penyakit kardiovaskuler, stroke dan kaki diabetik (King et al 2016;Ramesh et al 2015;Mansour et al 2014;Djrolo et al 2014). Diabetes bahkan dapat dikaitkan dengan peningkatan mortalitas akibat timbulnya beberapa kanker seperti kanker payudara, kanker usus buntu (colorectal cancer) dan kanker prostat (Spangler & Kirk 2014).…”
Section: Pendahuluanunclassified